Apollo : the epic journey to the moon - Reynolds, David West. (New York : Harcourt, 2002)
An illustrated retrospective of the Apollo missions, which peaked in 1969 with the historic moon landing, looking at the people and technology involved in the program of lunar exploration.
"A Tehabi Book."
Includes bibliographical references (p. 266-267) and index.
Library Journal, April 2002
Booklist, March 2002
Choice, November 2002
Young Adult
Keywords: Apollo project -- History; Space flight to the moon